Expressway to Power: Infrastructure Projects and Political Support - Mevlude Akbulut-Yuksel; Dozie Okoye; Belgi Turan (Institute of Labor Economics (IZA), 2020)
This paper provides causal evidence on how political parties consolidate power in an electoral democracy. We collect administrative data on expressway construction by the Justice and Development Party (AKP) in Turkey, and use province-by-year variation in expressway construction to show that vote shares for the AKP increased in response to the expressways. For the average province in which the length of the expressway network increased from 51km to 193km, the estimates imply that the expressway expansion increased the AKP's vote share by 4.2 percentage-points or one-third of the increase from 2002 to 2011. Electoral gains by the AKP primarily came at the expense of its more established rivals. The estimates account for province and year fixed effects, which allows us to control for any fixed province characteristics and time-specific factors that might be related to expressway expansion and vote shares. We further show that the estimates are robust to arbitrary region-specific time trends, province-specific quadratic time trends, and are not driven by province-by-year variation in other investments undertaken by the AKP. Examining mechanisms, we do not find evidence that increased economic growth due to the express-ways drove increased vote shares for the AKP. We find evidence that the visibility and success of the expressway expansion project signalled competence and stability. The electoral benefits of the expressway were stronger in provinces that experienced greater political instability between 1995 and 2002, losses for the rival parties were greater in provinces they previously controlled indicating changes in perception, and there were no similar electoral gains to less visible projects.
Keywords: H54; N45; N95; O18; P16; 330; expressways; political economy; voting; Turkey